CONTROLLING AS A MANAGEMENT TOOL FOR ENTREPRENEURIAL ACTIVITIES ON THE BASIS OF CORPORATE SOCIAL RESPONSIBILITY - Butenko, Daria; Konstantynovskyi, Leonid (Social Economics, 2025)
The purpose of the article is to substantiate the role and determine the significance of controlling as an effective tool for managing entrepreneurial activities in the context of implementing the principles of corporate social responsibility. The paper identifies the main tasks, functions, and types of controlling, analyzing its impact on optimizing business processes, improving economic efficiency, and ensuring sustainable enterprise development. The article examines controlling as a key management tool based on the principles of corporate social responsibility. The research highlights the importance of controlling in supporting managerial decision-making through optimized information flows, improved monitoring, planning, and control. An analysis of the genesis of controlling and its implementation specifics in Ukraine is provided. The article systematizes the tasks, functions, and structure of controlling systems, encompassing goal setting, business process planning, management accounting, deviation analysis, and control. The role of controlling in the realization of corporate social responsibility principles is given particular attention. This includes ensuring the positive impact of enterprises on society, the economy, and the environment. It is noted that controlling can be applied not only as a tool for operational decision-making but also as a mechanism for managing the effectiveness of corporate social responsibility. The article explores the primary types of controlling ‒ strategic, tactical, operational, and dispositional ‒ and emphasizes their importance in achieving both short-term and long-term business goals. Strategic controlling focuses on generating information about potential development directions, tactical controlling addresses the tasks of strategic management, while operational and dispositional controlling coordinates daily business processes. The study also emphasizes the importance of controlling as a tool for assessing energy-saving programs, waste management, community impact, and ensuring ethical business standards.